Personnel Management as a Priority Management at the University Library of the Future - Sequeira Ortiz, Deyanira (1993)
University library directors face the strategic problem of deciding what university libraries will look like in the next 10 years, and what actions must be taken in the next five years if that future is to be achieved. There has begun to be a shift in the rapid growth of information technology, electronic access to information, and the academics' service station concept. University libraries need to develop new projects and services so that they can make the change from a mode of production of services to a mode of production as information facilitators. This implies a reconceptualization of the role of the university library, the role of the user, and that of library staff. New staff profiles will be needed and there will be a priority task of retraining and development of employees, essential aspects in the reformulation of the future library.